The appropriate counseling on prenatal screening test for foreign women in Emilia-Romagna - Menichini, Daniela; Sciutti, Giovanna; Miano, Maria Vittoria; Ricchi, Alba; Infante, Ramona; Molinazzi, Maria Teresa; Bertucci, Emma; Facchinetti, Fabio; Neri, Isabella (Acta Biomedica Atenei Parmensis, 2021)
Objective: The increase in the migratory phenomenon entails the need to adapt obstetric care to the population which includes foreign pregnant women. In this context, it emerged a little adherence to the prenatal screening test among foreign women compared to Italian women, which is assumed to be attributable to an inadequate counseling. This study aims to evaluate midwife’s perception of the counseling effectiveness in foreign women for the combined test and subsequently assess its adequacy through an external evaluation. Methods: this is a cross-sectional study conducted from September to November 2019. An ad hoc questionnaire was administered to midwives working in the territorial district of the Emilia-Romagna Region, investigating their counseling skills. Then an external evaluation of the counseling was conducted by observing the interview between the midwives and the patients (N = 10), to analyze its appropriateness. Results: Seventy-five midwives completed the questionnaire with a positive response rate of 57.2%. In general, 69.3% of midwives are satisfied with the training received from the regional course, but 85% found many difficulties in counseling foreign women. The 14% of midwives state that they always have the cultural and linguistic mediator available and 44% of them state that they use brochures translated into several foreign languages. In the interviews observed, the counseling to foreign women was found to be shorter and more limited than that provided to Italian women. Conclusions: Most of the consulting midwives declare that they feel prepared to perform a correct prenatal counseling also for foreign women, but the external evaluation of the interviews, and the regional data on adherence to the antenatal screening of foreign women, show many critical points. It becomes necessary to carry out further studies that investigate not only the counseling skills of midwives, but also the needs of assisted women about prenatal diagnosis.